Functional characterization and phenotyping of RAB2A and Lactadherin/MFGE8 as boar sperm zona pellucida binding proteins - Zelenkova, Natalie; Kraus, Veronika; Ded, Lukas; Spevakova, Daniela; Sadilkova, Lucie; Frolikova, Michaela; Pilsova, Aneta; Pilsova, Zuzana; Klusackova, Barbora; Simonik, Ondrej; Chmelikova, Eva; Krejcova, Tereza; et al. (Frontiers in Cell and Developmental Biology, 2025)
Mammalian fertilization begins with the species-specific binding of spermatozoa to the oocyte’s zona pellucida (ZP), a process mediated by multiple surface proteins forming a functional receptor complex. Among them, the Ras oncogene family protein RAB2A and lactadherin/MFGE8 (p47/SED1) were previously identified as ZP-binding candidates in pig; however, their functional roles in sperm-oocyte interactions remained unconfirmed. This study aimed to evaluate their involvement in sperm-ZP binding by using antibody-blocking and competitive binding assays with porcine oocytes. In parallel, we validated the specificity and functional relevance of two in-house raised monoclonal antibodies, 5C5 and 1H9, targeting RAB2A and lactadherin/MFGE8, respectively, and further characterized these proteins in boar spermatozoa. Immunofluorescence detection indicated that both RAB2A and lactadherin/MFGE8 became accessible on the sperm surface upon capacitation. Their surface localization at this stage supports their potential involvement in the primary sperm-ZP interactions preceding acrosomal exocytosis. Moreover, the sperm-specific 5C5 antibody detected reduced RAB2A levels in ejaculates from men with abnormal sperm parameters. This highlights the potential of RAB2A as a biomarker of sperm quality and acrosomal integrity, with promising translational relevance from animal models to humans. In vitro sperm-zona binding assays revealed that while in-house raised antibody treatments showed no significant inhibition, follow-up experiments using a commercial anti-RAB2A antibody demonstrated a significant reduction in sperm binding to the ZP of the oocyte. Both recombinant RAB2A (rc-RAB2A) and recombinant lactadherin (rc-lactadherin) significantly reduced sperm-ZP binding, highlighting their functional relevance. Our results support the role of RAB2A and lactadherin/MFGE8 in sperm-oocyte binding and highlight the utility of monoclonal antibodies 5C5 and 1H9 for sperm phenotyping. Future work should focus on identifying molecular interaction partners and signaling mechanisms that mediate the initiation of acrosomal exocytosis at fertilization.